A systematic review of the effects of postnatal maternal anxiety on children - Glasheen, Cristie (2009)
Several decades of research have focused on the impact of exposure to postnatal depression on children, while anxiety has been largely overlooked. Estimates of the prevalence of postnatal maternal anxiety (PMA) range from 3% to 43%, suggesting PMA may be an important risk factor for adverse outcomes in children. This review summarizes what is known about the effects of PMA exposure on children and makes recommendations for future research. A systematic search of Ovid MEDLINE(®) and PsychINFO(®) through 2008 identified 18 studies that evaluated child outcomes associated with PMA exposure. Identified studies covered three domains: somatic, developmental, and psychological outcomes. The strongest evidence for an adverse effect of PMA exposure is in somatic and psychological outcomes; the evidence for an effect of PMA on child development is inconclusive. Methodological differences among the studies make comparisons difficult and there are a number of common limitations that challenge the validity of these studies.